Evangelicalismo e cultura escrita: o papel dos fanzines na construção de uma identidade contracultural cristã em Belo Horizonte entre os anos 1980 e 1990 - Jaime Magalhães Sepulcro Júnior (2019)
This research aimed to understand the role of the written culture, especially fanzines, in the construction of a christian counterculture identity in Belo Horizonte between the years 1980 and 1990, period which includes the emergence and consolidation of the Comunidade Cristã Caverna de Adulão (CCCA), one of the Brazilian exponents of the artistic, cultural and ecclesiastical movement known as christian counterculture. The movement consists in an “encounter” between the young American counterculture of the 1960s and the American evangelical youth, resulting in a christian artistic and musical explosion filled with elements of the counterculture, such as the hippy aesthetic and language, the progressive rock, in a process of re-signification of the traditional protestant practices and, consequently, at the creation of alternative churches. It is considered that the movement came to Brazil in the 1970s and developed in the following years, parallel to the transformations of the secular counterculture, seeking to incorporate their musical genres and the identities that have emerged with them in the national and international scenarios. The research is carried out from the perspective of Cultural History and the field of study on the history of written culture. The concept of mobilized identity starts from the perspective of cultural studies. The sources of the research were constructed from oral testimonies collected in interviews and from written documents such as letters, cassette inserts and CDs, posters, magazines and, mainly, fanzines of the movement produced in the scenario of Belo Horizonte. Throughout the analysis, the fanzines proved to be a privileged means of transmitting the representations of the movement in a systematized way insofar as they deal with various themes related to the christian counterculture universe and carry out religious practices (discipleship and evangelization) and cultural practices related to the underground universe (criticism and apologies), directing his discourse simultaneously to two public readers (the christian and the non-christian). This type of written production, therefore, played a significant role in the construction of the identity of the movement especially in the 1990s, not only in the local scenario, but also at the national level, considering the breadth of its circulation. The representations conveyed in the fanzines acted in the construction of a youthful, urban, underground and evangelical identity.